TRANSMISI BAURAN KEBIJAKAN BANK INDONESIA PADA STABILITAS HARGA - Yuliati, Lilis; Lestari, Endah Kurnia; Maulana, Reza Bagas (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to analyze Bank Indonesia monetary and macroprudential policy mix in achieving price stability as the goal of the policy.Design/methodology/approach- The variables were used in this study are inflation rate, asset price, exchange and credit rate, and inflation expectation, while the instrument used is the BI Rate which represents the monetary policy and GWM LDR which represents macro-prudential policy. The analysis method uses VAR by using data from the 2011M4-2018M5 periods.Findings- The VAR estimation showed that BI Rate affected the inflation rate through asset price, exchange rate, and credit. The GWM LDR instrument affected the inflation rate through asset price and credit. The IRF test showed that the shock on the BI Rate instrument was responded as negative by the inflation rate with 5 months lag, while the shock on GWM LDR as the macroprudential policy instrument was responded as negative by the inflation rate with 2 months lag. Implications- This indicates that the mix of monetary and macroprudential policy instruments can be used by BI in achieving its final policy objectives, and exploration of the selection of instruments used is needed. The findings show inflation expectations have a significant negative effect on the inflation rate in transmitting monetary policy by BI.Keywords: Policy Mix, Price Stability and VAR